Psychological Experiences During Previous High School Sport Participation Predict College Students' Current Psychological Health - Jonathan DeFreese; Amanda Visek; Nikki Barczak-Scarboro (Bowling Green State University, 2022)
Adolescent sport participation has been positively associated with psychological health outcomes. Yet, further research is needed to explore how psychosocial health benefits from sport may be maximized or minimized based on one's psychological experiences during previous sport participation. The present study examined associations among retrospective psychological experiences of high school sport participation and markers of current college students' psychosocial health. American college students (N = 300) self-reported retrospective high school sport experiences (i.e., burnout, engagement, and stress) and current psychosocial health outcomes (i.e., social support, depressive symptoms, life satisfaction) via an online interface. Moderated multiple regression analyses showed high school sport burnout, stress, and engagement to predict significant variance in college social support (p < .05), anxiety (p < .01), depressive symptoms (p < .01), and life satisfaction (p < .01). Results provide evidence that retrospective accounts of high school sport participation experiences (i.e., low burnout, low stress, and positive engagement) were associated with more adaptive post-high school psychosocial outcomes in college. This information may guide future prospective studies and aid practitioners by proving a broader understanding of psychosocial outcomes of sport participation.